Developing a Self-Management Skills Enhancement Program for Primary School Learners - Wenjing Jiang; Edward Jimenez (International Journal of Education and Humanities, 2026)
This study analyzed the implementation of a self-management skills program and the multifaceted performance of primary school learners at Dongchang Road Primary School, Shandong, China. It aimed to describe learners' demographic profiles by age, gender, and grade level. It also assessed the level of program implementation for self-monitoring, self-evaluation, and self-reinforcement mechanisms. Further, it determined learners' levels of self-control, self-confidence, and self-worth, identified differences in multifaceted performance across demographic variables, examined the significant effects of self-management skills on multifaceted performance, and developed a proposed self-management skills development program. A descriptive correlational design with regression analysis was used to examine relationships among the variables without manipulation. The participants were in Grades 4-6 of a primary school. The data were analyzed using frequency and percentage, mean and standard deviation, Mann–Whitney U test, Kruskal–Wallis test, and multiple linear regression with bootstrapping. The findings showed that a developmentally appropriate, well-balanced sample had nearly equal representation across all grade levels. The self-management skills program was implemented to a very great extent, and learners demonstrated very high levels of self-control, self-confidence, and self-worth. No significant differences in multifaceted performance were found across age, gender, or grade level. The regression analysis showed that selective, dimension-specific effects on self-evaluation significantly enhanced self-control, whereas self-reinforcement positively influenced self-confidence but was negatively associated with self-control. No self-management component independently predicted self-worth or overall multifaceted performance. Thus, based on the findings, a balanced and integrative self-management skills development program is proposed. It emphasizes reflective self-evaluation, guided reinforcement, and emotionally supportive classroom practices for learners